The Effectiveness of Differential Transform Method (DTM) on Solving The Duffing Equation. - Nurazlin Nazifah Mohd Faizal Anemee; Noor Azliza Abd Latif (Enhanced Knowledge in Sciences and Technology, 2022)
In this paper, a semi-analytical solution called differential transform method (DTM) is applied to solve the Duffing equation. We solved examples of Duffing equation with the homogeneous, linear and trigonometric function. The solution is obtained semi analytically by using the DTM with aid of Excel and Maple 15. Maple 15 also used to compare the DTM solution and the exact solution by displaying the numerical results and graphical outputs. The accuracy of the DTM is compared to the exact solution or other methods done by previous researcher. By the end of the research, it showed that the DTM is able to solve the Duffing equation and obtain result close to the exact solution. However, convergence speed towards the exact solution only to small parameter.